LA SITCOM O COMEDIA DE SITUACIÓN: ORÍGENES, EVOLUCIÓN Y NUEVAS PRÁCTICAS - Graciela PADILLA CASTILLO ,Paula REQUEIJO REY (Fonseca, Journal of Communication, 2023)
The situation comedy or sitcom (a term that is popularly known in English and that arises from the contraction of the words "situation" and "comedy") is one of the most successful genres within the series